Effects of 5.8 GHz Microwaves on Testicular Structure and Function in Rats. (6th June 2022) - Xue, Yizhe; Guo, Ling; Lin, Jiajin; Lai, Panpan; Rui, Gang; Liu, Liyuan; Huang, Rongrong; Jing, Yuntao; Wang, Fuli; Ding, Guirong
Abstract : Objective . To investigate the effects of exposure to 5.8 GHz microwaves on testicular structure and function of male adult rats. Methods . After 30 days of exposure, we evaluated sperm quality by determining sperm concentration and quantifying the number of abnormal sperm. Testicular morphology was investigated by hematoxylin-eosin (HE) staining. The levels of testosterone (T), follicle-stimulating hormone (FSH), luteinizing hormone (LH), glial cell line-derived neurotrophic factor (GDNF), stem cell factor (SCF), and transferrin (TRF) were determined by enzyme-linked immunosorbent assays (ELISAs). We also used western blotting to determine the levels of GDNF and SCF and apoptosis-related protein (caspase-3) in the testis. Results . Compared with the sham group, there were no significant differences in terms of sperm count, sperm abnormality, and the levels of T, FSH, LH, GDNF, SCF, and caspase-3 in the microwave group. Conclusion . Under the experimental conditions, 5.8 GHz microwave exposure has no obvious effect on testicular structure and function of rats.